2010
DOI: 10.1107/s1600536810010895
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 2,3-di-O-acetyl-4-O-levulinoyl-1-O-(2,2,2-trichloro-2-iminoethyl)-L-idopyranosiduronate

Abstract: In the title compound, C 18 H 22 Cl 3 NO 11 , a novel derivative of lidopyranosiduronic acid, the six-membered ring adopts a chair conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Atomic numbering for all molecules of compound 1 is shown in Fig 3 and (Table 2). This latter motif is similar to that reported in the crystal structure of methyl 2,3-di- [17]. By contrast, Form ІІ is characterised by the absence of hydrogen bonds when forming the crystal lattice.…”
Section: Resultssupporting
confidence: 62%
“…Atomic numbering for all molecules of compound 1 is shown in Fig 3 and (Table 2). This latter motif is similar to that reported in the crystal structure of methyl 2,3-di- [17]. By contrast, Form ІІ is characterised by the absence of hydrogen bonds when forming the crystal lattice.…”
Section: Resultssupporting
confidence: 62%
“…16−18 Nuclear magnetic resonance (NMR) investigation reported that the processes of binding and recognitions are sometimes governed through the nonchair forms, e.g., the L-iduronic residues of the anticoagulant GAG can activate the antithrombin III by adopting the skew-boat 2 S O ring conformer. 19 Among GAGs, the most prevalent GAGs are chondroitin sulfate (CS) and heparan sulfate (HS), and their major target proteins are chemokines, axon guidance molecules, cell-surface receptors, and growth factors. 14,20,21 While most attention has been paid to various HS−protein interactions, much less has been given to CS.…”
Section: Introductionmentioning
confidence: 99%
“…The epimerization and sulfation add massive heterogeneity and distinct topologies in the GAG population, which further affects human health and disorders. In this context, sulfation is a dynamic and complex post-translational modification process occurring at various positions within the backbone of GAGs and modulates extracellular signal . GAG conformational flexibilities, to some extent, additionally arise from the distortion of the pyranose rings associated with the ring pucker. Nuclear magnetic resonance (NMR) investigation reported that the processes of binding and recognitions are sometimes governed through the nonchair forms, e.g., the l -iduronic residues of the anticoagulant GAG can activate the antithrombin III by adopting the skew-boat 2 S O ring conformer . Among GAGs, the most prevalent GAGs are chondroitin sulfate (CS) and heparan sulfate (HS), and their major target proteins are chemokines, axon guidance molecules, cell-surface receptors, and growth factors. ,, While most attention has been paid to various HS–protein interactions, much less has been given to CS.…”
Section: Introductionmentioning
confidence: 99%